THE IMPORTANCE OF ARTIFICIAL INTELLIGENCE IN PRIMARY EDUCATION - Hadiamsyah, Yudhi; Meidina, Ahmad Rezy (Indonesian Journal of Islamic and Social Science, 2025)
The author focuses on the urgency of integrating AI in the context of primary education in Indonesia, specifically how AI has the potential to improve the quality of teaching and learning processes, educational administration, and provide personalized learning experiences for students. This research uses a descriptive qualitative approach with a primary literature review method. The research findings indicate that AI can assist teachers in implementing adaptive learning, managing academic data, and providing direct feedback to students. The implementation of AI also presents challenges, such as the need for digital infrastructure, teacher training programs, and the ethical use of student data. Strategic planning and sound cross-sector collaboration are necessary to integrate AI into primary education for effective and sustainable implementation. This article is expected to spark further discussion on the use of AI to transform primary education in Indonesia.